INTERPRETASI DAN KORELASI DATA RESISTIVITAS UNTUK MENENTUKAN LAPISAN AKUIFER DI RT.002/RW.002 KELURAHAN AMBAN KABUPATEN MANOKWARI PROVINSI PAPUA BARAT - Brian Rainstra Maay; Jance Murdjani Supit (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2021)
Aquifer layer modeling is a comprehensive study of the condition of the subsurface layer which is applied conceptually and aims to provide an overview of the pattern of the aquifer layer. The purpose of this study is to know how to model the subsurface layer and to determine the depth of the aquifer layer based on the resistivity value in RT.002/RW.002 Amban Village, Manokwari Regency, West Papua Province. The configuration used in this study is a dipole-dipole configuration. The results show that there are three layers, namely clay with a thickness of 0 – 2.6 m, limestone 2.6 – 37.5 m and sandstone 37.5 – 44.5 m. The aquifer layer is in the third layer, namely sandstone. It is estimated that this layer is a free aquifer which is limited by an impermeable layer above and at the bottom of semi-waterproof at a depth of 25-44.5 m.